PENGARUH KUALITAS PRODUK, PERSEPSI HARGA TERHADAP KEPUASAN PELANGGAN DAN DAMPAKNYA PADA LOYALITAS PELANGGAN (Studi Pada Konsumen Wardah Kosmetik di Toko Candra Jl. Pandanaran Semarang) - Jihan, 15.05.51.0356; Sholiha, Euis (Students Journal of Economic and Management, 2018)
This study aims to analyze the Influence of Product Quality, Price Perception towards Consumer Satisfaction and Its Impact On Consumer Loyalty. This research method using purposive sampling, with criteria of consumer age more than 17 years old and consumers who ever bought Wardah product in Toko Candra. The number of research samples are 100 respondents. The data test is done by instrument test consisting of validity test and reliability test. Furthermore, the test of regression analysis with F test, coefficient of determination test and t test. Based on the result of hypothesis test: product quality has positive significant effect to Consumer Satisfaction. Price perception have positive significant effect to Consumer Satisfaction. Consumer Satisfaction Influence have positive significant effect to Consumer LoyaltyKeywords: product quality, price perception, promotion, consumer satisfaction, consumer loyalty